Prevalencia y focos endémicos de brucelosis bovina en el cantón Pasaje - Acaro Suquisupa, José Ramiro (2007)
The present investigation about prevalencia and points endemics of Brucelosis bovine in the canton Pasaje, to realized in the different parroquias the canton, the objective: to determine the prevalencia of Brucelosis bovine in the canton and to locate points signs of Brucelosis bovine in the map ecological. To identifity and registration the animals to sample, to extract five to seven cc of blood of vein yugular of each animal, for extract the serum blood to use in the Card Test, presently with capilar of 6,5 cm of large and the serum blood to deposit in the stall of plaque ( 10 stall for each plaque), to proceed to place one drop of antigeno with help of toothpick for each sample, to proceed to give movement of rotation soft till which to pass four minutes, which is to time ideal for to realize the reading. The result to obtain after of examine 600 animals in the diferents parroquias of canton, 0 % of prevalencia.